2013
DOI: 10.1021/jm401485p
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Odds of Success in Drug Discovery: Choosing the Best Compounds for in Vivo Toxicology Studies

Abstract: A set of molecules that advanced into exploratory animal toxicology studies (two species) was examined to determine what properties contributed to success in these safety studies. Compounds were rigorously evaluated across numerous safety end points and classified as "pass" if a suitable in vivo therapeutic index (TI) was achieved for advancement into regulatory toxicology studies. The most predictive end point contributing to compound survival was a predicted human efficacious concentration (Ceff) of ≤250 nM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…There is a third category in practice where drug candidates cause a relatively high incidence of transaminase elevations in early clinical trials that were not detected in nonclinical safety assessment studies. Trying to mitigate these risks are the subject of many initiatives within the pharmaceutical industry that can vary in their approach . Integrating these approaches into decisions regarding medicinal design and compound selection is important since standard animal models only predict about 55% of human transaminase elevations.PF‐04895162 (ICA‐105665, discovered by Icagen, Inc., Durham, NC), is a novel small molecule that showed signs of efficacy for the treatment of epilepsy by opening neuronal Kv7.2/7.3 and Kv7.3/7.5 potassium channels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a third category in practice where drug candidates cause a relatively high incidence of transaminase elevations in early clinical trials that were not detected in nonclinical safety assessment studies. Trying to mitigate these risks are the subject of many initiatives within the pharmaceutical industry that can vary in their approach . Integrating these approaches into decisions regarding medicinal design and compound selection is important since standard animal models only predict about 55% of human transaminase elevations.PF‐04895162 (ICA‐105665, discovered by Icagen, Inc., Durham, NC), is a novel small molecule that showed signs of efficacy for the treatment of epilepsy by opening neuronal Kv7.2/7.3 and Kv7.3/7.5 potassium channels .…”
Section: Introductionmentioning
confidence: 99%
“…Trying to mitigate these risks are the subject of many initiatives within the pharmaceutical industry [2][3][4] that can vary in their approach. [5][6][7][8] Integrating these approaches into decisions regarding medicinal design and compound selection is important since standard animal models only predict about 55% 9,10 of human transaminase elevations.PF-04895162 (ICA-105665, discovered by Icagen, Inc., Durham, NC), is a novel small molecule that showed signs of efficacy for the treatment of epilepsy 11 by opening neuronal Kv7.2/7.3 and Kv7.3/7.5 potassium channels. 12 In nonclinical studies, only a single 7-day exploratory toxicity study in rats showed a dose-dependent alanine aminotransferase (ALT) elevation that was not accompanied by any histological correlate.…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis, there was a threefold enrichment in toxic compounds (in which toxic compounds were defined as those causing an adverse histological change or death) when logP was >3, but tPSA had little or no influence. A subsequent study from Pfizer has suggested that compounds that achieve efficacy at lower concentrations are more likely to progress through toxicology studies, and it further suggested that a predicted human efficacious total plasma concentration of <250 nM was indicative of a greater chance of success 15 .…”
mentioning
confidence: 99%
“…Finally a recent paper from Pfizer is worth highlighting [27]. It addresses the issue of what is the typical efficacious concentration (C eff ) of a drug that successfully passes through animal tox studies.…”
Section: Further Insight Into Controlling These Addictions In Drug DImentioning
confidence: 99%